Faktor-Faktor Yang Berhubungan Dengan Kualitas Tidur Pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Sam Ratulangi Manado - Clarina Theresia Kumontoy; Fima L. F. G. Langi; Sri Seprianto Maddusa (STIKES Columbia Asia Medan, 2026)
overlooked among university students. More than 60% of students consistently report poor sleep quality throughout their academic studies. A prior study at FKM Sam Ratulangi University (2020) identified stress as a factor related to sleep quality; however, simultaneous multivariate analysis of multiple determinants remains limited in the Manado region. Objective: To analyze factors associated with sleep quality among students of the Faculty of Public Health, Sam Ratulangi University (FKM UNSRAT), Manado. Method: A cross-sectional observational study was conducted among 256 active students of FKM UNSRAT Manado. Data were collected through an online structured questionnaire via Google Forms from September to December 2025. Statistical analysis using R version 4.5.3 included descriptive analysis, bivariate (Pearson) correlation, multivariate linear regression with stepwise forward selection, and network analysis (Gaussian Markov Random Field with graphical LASSO). Results: The median subjective sleep quality score was 5 out of 10, with an average sleep duration of 6 hours per night. The regression model identified four determinants of sleep quality: sleep duration (β=0.79; 95% CI 0.65–0.93; p<0.001), learning motivation (β=0.26; 95% CI 0.14–0.38; p<0.001), and physical activity (β=0.14; 95% CI 0.03–0.25; p=0.011) showed positive associations; while academic screen time (β=−0.07; p=0.005) showed a negative association. Conclusion: Students' sleep quality is influenced by the complex interaction of health behaviors, academic activities, learning motivation, and digital technology use. Preventive interventions should simultaneously target increased sleep duration, physical activity, learning motivation, and limitation of academic screen time.